Вплив заліза на перетворення вугільної речовини під час раптового викиду - Бурчак, О.В.; Гордієнко, О.А. (Геотехническая механика, 2012)
В работе предложен механизм генерации флюидов в процессе выброса. Оценено участие железа в процессах проходящих в молекулярной структуре угольного вещества при газодинамическом явлении. Рассмотрен энергетический аспект структурных трансформаций угольного вещества характерный для внезапного выброса. The mechanism of generation of fluids in the process of the troop landing is offered in the
work. Participation of iron in the processes of passing in the molecular structure of coal matter at the gas-dynamic phenomenon is appraised. The power aspect of structural transformations of coal matter which is a typical for the sudden troop landing is considered.